Effectiveness of Several Concentrations of Entomopathogenic Nematode (Steinernema spp.) On Mortality of Spodoptera exigua Hub. in Onions - Sunarto, Toto; Natawigena, Wahyu Daradjat; Irwan, Aep Wawan; Tyas, Widya Wening (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2023)
Spodoptera exigua is one of the main pests that attack onion. An alternative that can be done to control onion caterpillars is by using the entomopathogenic nematode (Steinernema spp.) that environmentally friendly. This research aimed to obtain the concentration of the entomopathogenic nematode Steinernema spp. that is most effective in causing mortality of S. exigua in onion plants. The experiment was carried out from January to August 2020 at Citeureup, North Cimahi, Cimahi City West Java. The method used in this research was an experimental method with a randomized block design, consisted of six treatments and four replications. The treatments (number of infective juvenile -IJ) were 0 IJ ml-1 (control), 1000 IJ ml-1, 2000 IJ ml-1, 3000 IJ ml-1, 4000 IJ ml-1, and 5000 IJ ml-1. The results showed that Steinernema spp. application at a concentration of 2000 IJ ml-1 was the most effective concentrations in causing S. exigua mortality in shallot plants (85.0 ± 5.0 %) at 72 hours after application. However, there was a tendency for treatment above a density of 2000 IJ ml-1 to decrease the mortality of S. frugiperda. Therefore, it is very necessary to consider the optimum population of nematoentomopathogens to produce high mortality of target insect pests.